Outcomes for trans students living in open housing - Wilson, Haley Lynette, author; Miller, Lisa, advisor; Johnson, Jen, advisor; Hudgens, Anne, committee member; Richards, Tracy, committee member (Colorado State University. Libraries, 2017)
Trans students have significantly varied campus climate experiences compared to cisgender heterosexual peers (Dugan, Kusel, & Simounet, 2012). This study focuses on the function of Open Housing, a gender non-specific housing option for trans individuals, on perceived outcomes. Residents of open housing participated in a brief demographic and satisfaction survey (N=10), and an interview regarding community outcomes (N=3). The participants were coded into LGBTQ+ and non-LGBTQ+ to determine identity-specific results. The data revealed a high population of first-generation students, transfer students, non-traditional students, and students with disabilities. Free response survey answers and interviews described five key themes including: (1) Community, (2) Relation to Others – interpersonal skill building and multicultural awareness, (3) Environment, (4) Self Development – identity awareness and positive self-regard, and (5) Authenticity. Responses indicate a lack of choice for trans students in choosing safety and validation of living in this Residential Learning Community, over other residential options. Participants demonstrated significant positive interpersonal and intrapersonal outcomes, and subsequent protective factors from living in the community, although causal or within-group analysis continues to be an opportunity for future research.
Keywords: LGBT; residential learning community; transgender; residence life; gender open housing; student affairs